IMPLEMENTATION OF THE TRI HITA KARANA CONCEPT IN THE MAPEED TRADITION AS HERITAGE TOURISM IN PAKRAMAN SUKAWATI VILLAGE, GIANYAR DISTRICT - I Putu Aditya Prawira Putra (UHN IGB Sugriwa Denpasar, 2025)
This article aims to explore the implementation of the Tri Hita Karana concept in the Mapeed tradition as part of the development of cultural heritage tourism in Pakraman Sukawati Village, Gianyar Regency. Tri Hita Karana, which includes the harmonious relationship between humans and God, humans and fellow humans, and humans and nature, is the basis for implementing the Mapeed tradition. Mapeed is a Balinese tradition of mutual cooperation to care for and clean temples as a form of respect for God, each other and the environment. This research identifies how the Tri Hita Karana principle is applied in Mapeed and its impact on cultural sustainability and the development of cultural heritage-based tourism. The research results show that the implementation of Mapeed, which is based on Tri Hita Karana, not only strengthens social relations between residents, but also plays an important role in preserving Balinese cultural values. On the other hand, Mapeed also has the potential to become a major attraction in the development of cultural heritage tourism in Pakraman Sukawati Village, by attracting tourists who are interested in authentic cultural experiences. This article concludes that Mapeed, which integrates Tri Hita Karana, can be an effective strategy in strengthening sustainable tourism, providing economic and social benefits for local communities, as well as preserving culture and the environment